Active and Intelligent Food Packaging Polymers - Souza, Victor G. L.; Pastrana, Lorenzo M.; Fernando, Ana Luisa (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint combines 11 quality review and research articles on active and intelligent food packaging polymers. We anticipate that the contributions gathered within this Special Issue not only reflect the current state of the field but also serve as a catalyst for future advancements. Together, we aim to unravel the intricacies of active and intelligent food packaging, paving the way for a safer, more sustainable, and technologically enriched future in the realm of food preservation.